2012
DOI: 10.1080/1385772x.2012.686693
|View full text |Cite
|
Sign up to set email alerts
|

Ring-opening polymerization of isopropylglycidyl ether (IPGE) with new catalysts of Ti, Sn, Al-alkoxides and comparison of its reactivity

Abstract: The polymerization reactions of isopropylglycidyl ether (IPGE) were carried out by various catalysts potassium hydroxide, potassium tert-butoxide, tetrafluorophthalate aluminum secbutoxide, tetrafluorophthalate tin tert-butoxide, and tetrafluorophthalate-titanium isopropoxide complexes. Tetrafluorophthalate-aluminum, tin, and titanium have been prepared from aluminum sec-butoxide, tin tert-butoxide, and titanium isopropoxide in alcohol and tetrafluorophthalic acid. Poly-IPGE and catalysts were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, high cost and discontinuous degradation rate are the key factors limiting wider applications of PPDO, for example, controlled release of drug. Graft copolymerization [13][14][15][16][17][18][19] is a versatile method to modify the PPDO for providing functionality to the resulting polymers, and for regulating polymer properties. However, there are few reports about graft copolymerization of PPDO with other polymers [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, high cost and discontinuous degradation rate are the key factors limiting wider applications of PPDO, for example, controlled release of drug. Graft copolymerization [13][14][15][16][17][18][19] is a versatile method to modify the PPDO for providing functionality to the resulting polymers, and for regulating polymer properties. However, there are few reports about graft copolymerization of PPDO with other polymers [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many studies have reported creating effective metal-based initiators (Figure 2) and their re-activities. 10 Metallic alkoxides such as Sn, 42,43 Al, 44,45 Zn, 46 Ti, 47 Sc, 48 enzyme, 49 and other catalysts have made significant contributions to the ROP of cyclic esters.…”
Section: Ring-opening Polymerization Of Cyclic Esters Using Homogeneo...mentioning
confidence: 99%
“…As a result, many studies have reported creating effective metal‐based initiators (Figure 2) and their re‐activities 10 . Metallic alkoxides such as Sn, 42,43 Al, 44,45 Zn, 46 Ti, 47 Sc, 48 enzyme, 49 and other catalysts have made significant contributions to the ROP of cyclic esters. Metal‐based complexes show a greater ability to manipulate the polymer's properties like molecular weight, PDI, and microstructure than aforementioned catalysts 26 .…”
Section: Ring‐opening Polymerization Of Cyclic Esters Using Homogeneo...mentioning
confidence: 99%
“…The reactions were carried out similarly to the preparations of β-diketonate tin(IV) propoxide and tetrafluorophthalate tin(IV) butoxide complexes. [10,11] The formulations of compounds were determined by elemental analysis, FTIR, and NMR measurements. The number of oxo group was one for both compounds.…”
Section: Materials and Instrumentationmentioning
confidence: 99%